Geograficidade libertária em Élisée Reclus: contribuição heterodoxa à história da geografia - Pinto, José Vandério Cirqueira [UNESP] (2015)
The geographical thought of Élisée Reclus is marked by an heterodox speech connected to the theoretical condition and spatial pratice that confront with the hegemonic models of territorial arrangement. The science model developed by Reclus was not accepted by critical historiograph of the time, denying the effectivity of geography as a field of knowledge politically engaged for the transformation of geographical imbalances. On the other hand, this was the main role of geography to Reclus: to have na eminently social character, politically dissident, placed as subversive experience and spatial pratice, able to face the interference of hegemonic models. Therefore, we seek to investigate the libertarian character in this geographicity of Reclus, assessing the degree of acceptance of this heterodox thought, the factors that initiated the neglect of his work, and the impacts of this neglect in the dissemination of his spatial pratice of anarchist base. The geographicity concept can be understood as experience and spatial practice, as a reflection model about the relations resulting fron human activities in the environment, and with Reclus, the geographicity win libertarian dimension...